Bridging Training and Competence to Innovation: The Role of Affective Commitment in Driving Innovative Behavior: - Ari Widyarini, Margaretha; Didik Subiyanto; Syamsul Hadi (Profesional Muda Cendekia Publishing, 2025)
Research Aims: This study analyzes factors influencing innovative behavior and commitment among employees in the Procurement Division of Yogyakarta City. Specifically, it examines the effects of training and competence on innovative behavior and commitment, as well as the mediating role of affective commitment in these relationships. Design/methodology/approach: The main data collection method in this study is a structured questionnaire, which will be distributed to 50 respondents selected using a census technique. The sample in this study consists of employees in the Procurement Division of Yogyakarta City. This study uses analysis techniques with Structural Equation Modelling (SEM) using AMOS Version 22.0/Amos Graph. Research Findings: Training does not significantly affect innovative behavior or affective commitment. However, competence positively influences both, indicating that skill development fosters innovation and emotional attachment. Affective commitment enhances innovative behavior and partially mediates the competence-innovation link, while it does not mediate the training-innovation relationship. Theoretical Contribution/Originality: This study extends organizational behavior and HRM theories by highlighting the role of competence and affective commitment in driving innovation. It underscores how non-financial factors, like emotional attachment and skill development, contribute to workplace innovation, particularly in public sector organizations.. Keywords: Training, Competence, Affective Commitment, Innovative Behavior, Procurement